Experience of Adolescent Survivors of Childhood Cancer about Self-Care Needs: A Content Analysis - Leila Valizadeh; Vahid Zamanzadeh; Akram Ghahremanian; Saeed Musavi; Masumeh Akbarbegloo; Fang-Yu Chou (Elsevier, 2020)
Objective: In cancer care management, patients or their family are usually responsible for continuing health care. Achieving this goal requires identification of their self-care needs. The purpose of this study is to explore the perception of self-care needs of adolescent cancer survivors. Methods: This study was conducted by the qualitative content analysis method. Participants were 19 adolescent childhood cancer survivors and six parents, nurses, physicians, and charity institution staff from children teaching hospitals in Iran. Participants were selected through purposeful sampling, and individual semistructured interviews were used for data collection. Graneheim and Lundman stages of content analysis were employed for data analysis. Data were managed with the MAXQDA10 software. Results: Content analysis revealed nine subcategories as follows: (1) nutritional protection, (2) prevention from infection, (3) prevention from physical damage, (4) control over cancer recurrence, (5) informational needs, (6) pain management, (7) releasing positive thoughts, (8) continuing routine life, and (9) family protection. The first six subthemes were related to protection against physical distress, and the final three ones were related to protection against psychological distress. These two categories form one theme: "protective self-care need" as an essential self-care need in adolescent cancer survivors. Conclusions: Pediatric and school health nurses can prepare strategies to meet these needs by providing effective informational and psychosocial supports, and healthcare providers are able to check periodically the status of survivors care to provide second or third level of care to prevent escalation and incidence of the adverse outcomes of the disease.